Le contrôle judiciaire comme technique de participation des citoyens aux choix énergétiques - Lemieux, Denis (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
The purpose of this paper is to show how judicial review has been used in the last ten years as a participatory technique by citizens and groups in the decision making process of administrative and political decisions dealing with energy exploitation and use. In a first part, the author makes the point that judicial review is unadopted to that purpose. A second part reviews the recent case law. That review brings the author to the conclusion that the judicial forum was, by and large, an inappropriate one as far as participation was the avowed goal of plaintiffs and petitioners. But, in the last part of the paper, the author affirms that despite all these short-comings, the use of judicial review was often positive not as a technique of participation but as one which did facilitate participation at a subsequent stage, due to the wide publicity and comments, judicial and extrajudicial, surrounding the proceedings.